Waste materials in construction : WASCON 2000 : proceedings of the International Conference on the Science and Engineering of Recycling for Environmental Protection, Harrogate, England, 31 May, 1-2 June 2000 - Wainwright, P. J. (Peter John); Goumans, J. J. J. M.; Woolley, G. R. (Guy R.) (Waste management series (Amsterdam, Netherlands), 2000)
This volume presents the proceedings of the International Conference on The Science and Engineering of Recycling for Environmental Protection (WASCON 2000), of which a number of themes have been identified. All are inter-related and inter-dependent in so far as potential users of secondary, recovered or recycled material have to be assured that the material is environmentally safe and stable. It is the environmental challenge that forms a leading theme for the conference, and the themes of quality assurance and quality control support this aspect. In terms of use of 'recovered' materials, scie.